PENGARUH GAYA KEPEMIMPINAN PATERNALISTIK DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada PT Pos Indonesia Regional VI Semarang) - Prilly, Adhinda; Mas’ud, Fuad (Diponegoro Journal of Management, 2017)
Human resources quality of the company can be measured through employee performance.  Employee’s performance is one of  factors to achieve the company objectives. The factors that affect employee performance are paternalistic leadership style and organizational culture. This research aimed to analyze the effect of paternalistic leadership style and organizational culture on Employee’s performance with employee engagement as the intervening.This  research  were  done  at  PT  Pos  Indonesia  Regional  VI Semarang.  The  data collected from 71  respondent  by using  census. The data  were analysed  by using  double regression by 23th version of SPSS.The Result of this research showed that the effect of paternalistic leadership style and organizational  culture on  employee engagement (as variable intervening)  is positive and significant and the impact of employee engagement on employee’s performance is positive and significant.